(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
The study examined the student-teacher ratio and internal efficiency of public secondary schools in Ondo State, Nigeria. The study adopted a descriptive research design of the survey type. The population for this study consisted of all 258 public secondary schools in Ondo State, while the sample size consisted of 200 teachers and 20 principals selected in 20 public secondary schools in Ondo State. Two research instruments were used for the data collection. The instruments tagged ‘Student -Teacher Ratio Questionnaire” (STRQ), and inventory specifically designed and administered to the principals (or Vice-Principals) to request the enrolment of students from JSS.1 to SSS III. Face and content validity of the instruments were ensured by experts, while the test-retest method of reliability was adopted to determine the reliability coefficient of 0.81 for the STRQ. The data collected were analysed using descriptive and inferential statistics. The hypothesis was tested at 0.05 level of significance. The finding revealed that there was a significant relationship between the student-teacher ratio and internal efficiency of secondary schools. It was recommended that government and school administrators should ensure that teachers are made available for students to reduce overpopulated classes, and teachers should be provided with opportunities to attend seminars, conferences, and training that will equip the teachers to apply innovative ideas in the classrooms. The Teaching Service Commission should ensure that experienced teachers are employed in public secondary schools in the State. This will enable the teacher to monitor the students when the class size is not so large.